FACEBOOK AS A MEANS OF COMMUNICATION IN THE SOCIAL MEDIA ERA - Dinda Cantika; Nayla Zulpatinniamma (CV Grasta Glory, 2026)
This article explores how Facebook functions as a communication medium in today’s digital life, with special focus on usage patterns, communicative motives, and the platform’s bearing on users’ social relationships. A qualitative research method grounded in library research and semi-structured interviews of three purposively selected informants was employed to produce contextually rich data. The results of the research confirm that Facebook as a social media platform is still the dominant social network, and that it will continue to be a dominant channel by which people in various socio-demographic groups communicate and maintain social ties. Beyond mere interpersonal interaction, the platform serves an economic and community function as well as many other social and socializing functions, consolidating its role as a multifunctional communication infrastructure. Further analysis of interview data confirms that people interacting with Facebook are doing so as a conscious way of maintaining relational bonds amid geographical barriers; they are not just interested in receiving information. The authors find that as technology moves forward into 2026, Facebook becomes further intertwined with everyday communicative life and this has consequences for the ways in which digital sociality is theorized and studied.